Future economic outlook for the price of cow's milk in Mexico - González-Hernández, Vianey; Callejas-Juárez, Nicolás; Martínez-Castañeda, Francisco Ernesto (Ecosistemas y Recursos Agropecuarios, 2025)
In the present study, the price of milk was estimated deterministically and stochastically for the period 2023-2028, with the objective of analyzing the economic situation of cow's milk production in Mexico, through the univariate series statistical method of time (ARIMA). A base average price was established, as well as its confidence intervals reflected in the lower limit price and upper limit price. The statistical distribution that best explained the behavior of base prices was the geometric distribution, which was used to estimate the stochastic model. The price of milk is expected to have a deterministic average behavior of 9.38 ± 0.76 pesos per liter for the next six years. The above suggests a methodological approach through which the estimation of the price of agricultural products can be explored and improved to obtain a differentiated price based on quality effect.
Keywords: ARIMA; livestock; modeling; prospective; productivity